2019
DOI: 10.9734/sajrm/2019/v3i230080
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Zingiber officinale (Ginger) against Clinical Bacterial Isolates

Abstract: Aims: The objective of the present study was to investigate the phytochemical constituents and antibacterial activity of ginger extracts against some pathogenic bacteria responsible for Urinary tract infection. Study Design:  A total of 35 samples were collected from patients with UTIs and wound infections. Place and Duration of Study: The study was conducted at 2 hospitals in Baghdad from1/7/2017 to 1/9/2017 Methodology: The urine sample was collected using a sterile container, while a swap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Ginger has proven the cytotoxic potential in the current study because of saponins, steroids, alkaloids, and anthraquinones. These results are similar to the previous studies, 40 , 41 which reported that ginger has solid cytotoxic potential. As compared to other herbal products, ginger has secondary side effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ginger has proven the cytotoxic potential in the current study because of saponins, steroids, alkaloids, and anthraquinones. These results are similar to the previous studies, 40 , 41 which reported that ginger has solid cytotoxic potential. As compared to other herbal products, ginger has secondary side effects.…”
Section: Discussionsupporting
confidence: 93%
“… 5 The principal rationale for utilizing ginger was its direct antimicrobial action, suggesting that it can be used to treat various bacterial infections. 5 , 37 Mohammed et al 41 investigated the antibacterial activity of ginger extracts using n -hexane, ethyl acetate, ethanolic Soxhlet, and water as solvents and reported the significant antibacterial activity of ginger extracts. In comparison, Naseer et al 42 showed no significant differences in the antibacterial effects of ginger’s water and ethanol extracts on S. aureus and S. pyogenes .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some herbs and spices, including ginger and garlic, have been utilized to successfully preserve other perishable foods such as fish and meat, respectively (Brewer, 2011 ). A number of studies have also reported on the food preservation potential of ginger and garlic (Akintobi et al, 2013 ; Indu et al, 2006 ; Khashan, 2014 ; Mohammed et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the antimicrobial activity of ginger and garlic ( Akintobi et al., 2013 ; Indu et al., 2006 ; Khashan, 2014 ; Mohammed et al., 2019 ). There is wide spectrum of antibacterial activity of ginger rhizome against a range of Gram negative and Gram positive bacteria.…”
Section: Introductionmentioning
confidence: 99%